Ferritin in Stunting - Danny Ernest Jonas Luhulima; Louise Kartika Indah (International Journal of Health and Pharmaceutical (IJHP), 2026)
Stunting, as defined by the World Health Organization (WHO), is a form of chronic malnutrition characterized by a child’s length or height being more than two standard deviations below the median for their age group. While diagnosing stunting is relatively straightforward, the primary challenge lies in its prevention. Clinical assessment and laboratory investigations play an important role in predicting the risk of stunting. Basic laboratory evaluations include complete blood count, urinalysis, and routine stool examination. In addition, metabolic screening may involve random blood glucose, blood gas analysis, lactate, ammonia, ketone bodies, amino acid profiles, and urinary organic acids. Further investigations can include culture tests, iron profile, electrolyte levels, renal and liver function tests, thyroid hormones, infection screening, and immunoglobulin E (IgE) levels. Iron deficiency is a key contributing factor to stunting; therefore, its prevention is essential. Hemoglobin is a sensitive marker for detecting iron deficiency anemia, but it is not reliable for identifying early iron deficiency. Hemoglobin levels may remain within the normal range even when iron stores begin to decline, which can delay diagnosis if clinicians rely solely on this parameter. Serum ferritin is a more sensitive early marker, as its levels decrease in the initial stages of iron deficiency.